MORABA - Overview on DLR's Mobile Rocket Base and Projects - Stamminger, Andreas; Altenbuchner, Ludwig; Ettl, Josef; Jung, Wolfgang; Kirchhartz, Rainer; Turner, Peter (SpaceOps 2012 Conference, 2012)
Mobile Rocket Base (MORABA), a division of the Space Operations and Astronaut Training Department of DLR (Deutsches Zentrum für Luft- und Raumfahrt) provides the national and international scientific community with the opportunity to prepare and implement rocket and balloon born experiments. The fields of research includes aeronomy, astronomy, geophysics, material science and hypersonic research and are conducted in cooperation with a variety of international patners. In addition satellite missions can be supported by mobile tracking radars for trajectory determination and TT&C mobile ground stations. MORABA also offers a number of mechanical and electrical systems for use on rocket, balloon and short term satellite missions. During the last four decades more than 250 campaigns have been performed in Antarctica, Australia, Brazil, France, Greenland, India, Italy, Japan, Norway, Spain, Sweden and USA. Depending on the scientific objective, an appropriate launch range is selected and complemented or fully equipped with MORABA’s mobile infrastructure, such as launcher, telemetry and tracking stations. MORABA supplies the suitable converted military surplus or commercial launch vehicles, as well as all necessary mechanical and electrical subsystems to the customers. This paper gives an overview of the MORABA infrastructure for sounding rocket launching and satellite TT&C. A short survey of MORABA projects of the last two years and the next two years is also provided.